Provable secure trusted protocol for network storage - DUAN Xin-dong; MA Jian-feng (Tongxin xuebao)
A provable secure trusted protocol for NASD was proposed.The protocol will achieve authentication,key agreement and secure channel within two rounds among the server,the disks and the user.At the same time,the protocol could realize the platform authentication and platform integrity verification in the first round of protocol interaction,which would improve the efficiency of the protocol,and prevent the server from malicious attacks effectively.The analysis results show that the protocol is SK-secure by using CK model,which would increase the data confidentiality,integrity and no repudiation.